Role of dermoscopy in laser therapy - Shehnaz Z Arsiwala; Nazneen Arsiwala (Wolters Kluwer Medknow Publications, 2023)
Lasers have revolutionized the interventional dermatology field over the last two decades. Dermatologic conditions previously untreatable are now treated with lasers and lights. A large number of laser systems with advances in technologies have expanded applications of lasers for conditions like birth marks, acne scars, wrinkles, pigmentation, etc. Newer avenues and protocols are now set to treat skin conditions with lasers. The applicability of laser for any indication is dependent on laser tissue interaction which is well documented. For a successful outcome with laser therapy, a right end point of treatment should be achieved. The laser physician often adjusts parameters for laser therapy depending on tissue response, the ultimate aim being achieving optimum outcome with minimum side effects. Gadget based skin evaluation techniques are now an integral part of dermatology and are extending to interventional dermatology too. Application of dermoscopy before, during, and after lasers in various indications has been documented and reviewed. The representative cases highlighted in article emphasize the added dimension to non-invasive diagnostic capabilities of a dermatologist by enabling subsurface microscopy and enhancing therapy outcomes, and incorporation of these into daily practice offers value addition to not only evaluation but also gauging response to therapies. Use of dermoscopy before, during, and after laser therapies is an invaluable non-invasive tool to assess the right indication, initiate appropriate priming, achieve good end point, gauge untoward side effects, achieve good results, and engage patient confidentiality. Comparison of high magnification digital images is also enabled by digital videodermoscopy. Structured studies and protocols are needed to standardize the use of dermoscopy integrated with laser procedures.